Does the trained immune system play an important role in the extreme longevity that is seen in the Sardinian blue zone? - Soloski, Mark J.; Poulain, Michel; Pes, Giovanni M. (Frontiers in Aging, 2022)
Villages in the island of Sardinia in the Mediterranean that display exceptional longevity are clustered within a defined mountainous region. Because of their unique location we hypothesize that these villages had a unique infectious disease exposure relevant to the observed successful longevity. These highland villages had a significant exposure to malaria in the first half of the 20th century after which malaria was eliminated due to vector control mechanisms. In addition, there is likely a high incidence of Helicobacter pylori infections among shepherds in Sardinia, the primary occupation of many living in the LBZ, as well as helminth infections among children. This suggests that individuals living in the LBZ had a unique infectious disease exposure. Specifically, we hypothesize that the continued high exposure of residents in the LBZ to these infectious agents prior to the 1950s lead to the generation of a uniquely trained (or imprinted) immune system. Once some of these diseases were eliminated in the latter half of the century, individuals within the LBZ were equipped with a trained immune system that was uniquely capable of not only responding effectively to common infections but also responding in a manner that maximized maintaining tissue health. In addition, there are lifestyle factors that also favor such a trained immune system. This hypothesis may help explain the slow progression of chronic immune mediated diseases as well as other chronic non-transmissible age-related diseases seen in the Sardinian LBZ and serve as a template for future studies that support or refute this hypothesis.